MODERN OFFENSIVE PHILOSOPHY - Finch, Chris (Sport- és Egészségtudományi füzetek, 2025)
When you are coaching it’s all about selling your beliefs to the players. You need to create an offensive philosophy on certain principles: 1. How do we carry over to the floor 2. How do we install it 3. What drills do we do, that support is 4. How do we continue the messaging, that we are all buying into the same belief system A really important rule is to create an efficient offence. With modern analytics, the game is broken down into the 4 Factors: 1. How well you shoot - Effective Field Goal Percentage (eFg%) 2. How often do you get to the Free Throw line - FT. Rate 3. How often do you get your missed shots back - OREB% 4. How well do you take care of the ball - TO% In the modern game right now the three most efficient shots are layups, three point shots and free throws. It is really important to replace poor shot selection, with good shot selection. We need to make our decisions quickly - 0.5 mentality (drive, pass, shoot). We want to run after misses and makes - most teams run after turnovers and misses, but only the real committed teams run after makes. Sharing the floor and sharing the ball is key in offensive possession. To achieve this you need to be a movement team: run, cut and roll for our teammates. Besides this one of the most important parts of offense is spacing, and re-spacing, being early in our spots. Spacing is how we start, re-spacing is what happens after we start moving. Anything that you do should have a shared terminology, shared language builds culture. Using very catchy, easy messages that relate to our game is essential.